HISTORY OF THE DEVELOPMENT OF THE SYSTEM OF LAND LEGAL RELATIONS IN UKRAINE AND IDENTIFICATION OF ISSUES OF LAND DETERIORATION AND CONTROL OVER THEIR PRESERVATION - Pashko, Yulia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the proposed scientific research is to analyze the regulatory and legal support for changes in the field of land legislation and the development of the land protection system and their preservation in Ukraine. Research methods: dialectical and formal logic, historical and legal, system analysis and synthesis, generalization and modeling. Results: the problems of land ownership in Ukraine and the formation of the land protection system are identified. A historical analysis of the land protection system and its development is presented. The policy in the field of creation and development of legislation on land ownership in Ukraine, as well as the directions of formation of legislation on land protection, is studied. Individual approaches and experience in the system of land use and land ownership in the Russian Empire and the Soviet Union are analyzed, shortcomings are identified and a number of new approaches to solving the problems of land ownership and its protection are proposed. Discussion: since Ukraine is predominantly an agricultural country, the issues of land and land legal relations in Ukraine are one of the main ones. The issue of land protection, as well as legal relations in the field of land protection and restoration, the features of those used in agriculture, should be analyzed and studied in detail.